Connection between nuclear structure, dissipation, and time in fission data - Caamaño M.; Ramos D.; Fernández D.; Mantovani G.; Farget F.; Rodríguez-Tajes C.; Lemasson A.; Rejmund M.; Schmitt C.; Ackermann D.; Álvarez-Pol H.; Audouin L.; et al. (EPJ Web of Conferences)
Nuclear fission is still one of the most complex physical processes due to the interplay between macroscopic and microscopic nuclear properties that decide the output. An example of this coupling is the presence of nuclear dissipation as an important ingredient that contributes to drive the dynamics and has a clear impact on the time of the process. However, different theoretical interpretations and scarce experimental data make it poorly understood. At low excitation energy, the relative yields of fragments even and odd atomic numbers show a clear difference, which can be quantified with the so-called even-odd effect. This seemingly mundane property can be used to obtain information about the energy dissipated during the process and the role of structure in its dynamics. In this paper, the study of the even-odd effect for elasticand transfer-induced fission data is discussed. A clear connection with particular fragment shells and the dissipation energy is found, as detailed in Ref. [1]. In addition, preliminary results from quasi-fission data show the formation of a relatively large even-odd effect, which suggests a process with low dissipation mainly consisting in the exchange of nucleon pairs.